Expression, purification, and characterisation of a novel bacterial ADP-ribosyltransferase - Habib, Abdula (My University, 2023)
ADP-ribosylation is a chemical modification that is mostly known as a post-translational modification targeting nucleophilic amino acid residues. It utilizes the common coenzyme NAD+ as the reactant. The reaction is catalysed by ADP-ribosyltransferases (ARTs) which include bacterial AB-exotoxins also known as bARTTs (bacterial ART toxins). Exotoxins are proteins with enzymatic activity that are secreted or released upon lysis. They are secreted by pathogenic bacteria such as Corynebacterium diphtheria and Vibrio cholerae. Previously the Turku Cellular Microbiology Laboratory has discovered in silico open reading frames from different Bartonella species. The aim of my thesis is to express, purify and functionally characterise a putative open reading frame from Bartonella sp. 1-1C named CtxA. The N-terminally hexahistidine tagged CtxA constructs are transformed into an E. coli expression strain and purified with nickel-nitrilotriacetic acid (Ni-NTA) affinity chromatography followed by size-exclusion chromatography (SEC). The auto- and trans-ADP-ribosylation activity is studied with western blot assays. As a result of my studies the proteins were successfully purified and verified with anti-His western blot. Furthermore, both anti-MAR/PAR and biotin-ADP-ribose streptavidin western blots suggest that CtxA is a novel bARTT with auto-ADP-ribosylation activity. The target substrate for CtxA was not found despite the promising results from eukaryotic lysate studies.
Keywords: ADP-ribosylation, exotoxin, NAD+